An orally available cancer drug AZD6738 prevents type 1 diabetes - Sugitani, Norie; Mason, Hannah R.; Campfield, Brian T.; Piganelli, Jon D. (Frontiers in Immunology, 2023)
Type 1 diabetes (T1D) affects three million Americans, with 80 new people diagnosed each day. T1D is currently uncurable and there is an urgent need to develop additional drug candidates to achieve the prevention of T1D. We propose AZD6738 (ATRi), an orally available drug currently in phases I and II of clinical trials for various cancers, as a novel candidate to prevent T1D. Based on previously reported findings of ATRi inducing cell death in rapidly proliferating T cells, we hypothesized that this drug would specifically affect self-antigen activated diabetogenic T cells. These cells, if left unchecked, could otherwise lead to the destruction of pancreatic β cells, contributing to the development of T1D. This work demonstrates that increasing the duration of ATRi treatment provides extended protection against T1D onset. Remarkably, 5-week ATRi treatment prevented T1D in a robust adoptive transfer mouse model. Furthermore, the splenocytes of animals that received 5-week ATRi treatment did not transfer immune-mediated diabetes, while the splenocytes from control animal transferred the disease in 10 days. This work shows that ATRi prevents T1D by specifically inducing cell death in self-antigen activated, highly proliferative diabetogenic T cells through the induction of DNA damage, resulting in the inhibition of IFNγ production and proliferation. These findings support the consideration of repurposing ATRi for T1D prevention.